Multimodal Education: Philosophy and Practice, by Baranova, Jurate and Duobliene, Lilija - Luc, Anckaert (Acta Paedagogica Vilnensia, 2021)
Multimodal Education: Philosophy and Practice, by Baranova, Jurate and Duobliene, Lilija, Washington: The Council for Research in Values and Philosophy, 2021, ISBN 1565183495, 9781565183490.